Moving forward based on backward: Innovation in developing creative thinking assessments aligned with the curriculum - Firdha Mahrifatul Zana; Cholis Sa’dijah; Susiswo, Lathiful Anwar (Kasetsart Journal of Social Sciences, 2026)
This research and development aims to: (1) develop an assessment instrument based on alignment with the curriculum to measure students’ creative thinking, (2) validate the assessment instrument, and (3) calculate the level of reliability of the instrument when tested. The creative thinking assessment instrument was developed using the Research and Development (R&D) method design with a modified model from Zulkardi (2002). There are four stages in this design: the preliminary stage, prototyping stage, formative evaluation stage, and field test stage. The developed instruments were then analyzed qualitatively and quantitatively. Quantitative analysis was carried out to ensure the validity and reliability of the data. First, the method used by the researchers to determine the instrument’s validity is the Content Validity Index (CVI). This method consists of two indications, namely, the Item-level Content Validity Index (I-CVI) and the Scale-level Content Validity Index (S-CVI). A total of eight experts in the field of Mathematics and Mathematics Education from Malaysia and Indonesia were involved as assessors. Second, the ANATES 4.00 software was used to analyze data related to reliability, discriminant index, difficulty index, and alpha coefficient. 34 twelfth grade students in East Java were involved in this study. Other data sources were the results of semi-structured interviews. The study results showed that each item of the instrument developed was valid with an I-CVI value in the range of .87−1 and an S-CVI/Average value of .97. The ANATES 4.00 showed that the item had a high level of reliability. These results are supported by an alpha coefficient value of .82, an item discriminant index ranging from .55−.70, and a difficulty index ranging from .60−.67. Based on the findings, specific strategies for teachers or other authorities are needed to develop assessments that can train and measure students’ creative thinking considering that this skill is very much needed in the era of rapid development of science and technology.